Analysis on Entrepreneurship Psychology of Preschool Education Students With Entrepreneurial Intention - Yin, Yiwei; Yang, Liu; Liu, Bojing (Frontiers in Psychology, 2020)
To diversify the creative thinking of preschool education students and improve their ability to innovate and start a business, a survey of preschool education students under entrepreneurial psychology theory was conducted in this research. Based on the theoretical foundation of entrepreneurial psychology, this article analyzed the entrepreneurial psychological quality and psychological education of college students. By investigating preschool education students in a certain college in Sichuan as the research object, the author explored the current entrepreneurial intentions of college students and their entrepreneurial psychological problems. In response to the current entrepreneurial situation of college graduates, relevant countermeasures were proposed from the perspective of the school to support their entrepreneurial psychology. Among the 205 preschool education college students, the students were more willing to give full play to their professional expertise in terms of employment intentions. At the same time, there were still situations in which students were dissatisfied with the prospects of preschool education career development and wanted to achieve the value of life through other approaches. Most students in preschool education had a wait-and-see attitude toward entrepreneurship. Only 35% of students had a clear intention to start a business and made their plans for entrepreneurship. More than 90% of students held that they had developed inadequate entrepreneurial ability, and 80% of students believed that they lacked the required professional knowledge. These two factors constitute the main reasons for students’ negative attitudes toward entrepreneurship. Nevertheless, colleges may stimulate the potential of students’ self-development through the improvement of entrepreneurial psychological education courses, the construction of psychological consultation institutions on campus, and the establishment of interactive platforms for entrepreneurship. In this way, students’ entrepreneurial psychology can be cultivated in an all-round way. Therefore, to deal with the weak overall entrepreneurial consciousness of college students, the colleges should cultivate entrepreneurial innovative talents by strengthening the psychological education of entrepreneurship for students, and help college students achieve entrepreneurial success.